THE INFLUENCE OF LEARNING DISCIPLINE ON STUDENTS' LEARNING OUTCOMES - Osco Parmonangan Sijabat (Pande Nami Jurnal (PNJ), 2024)
This study aims to describe in depth related to learning discipline is a mental attitude that is reflected in the actions or behavior of individuals, groups or communities in the form of obedience to rules set by ethics, norms and rules that apply in society for certain purposes. The purpose of this study was to determine the effect of learning discipline on social studies learning outcomes for fifth grade students at SD Negeri 091523 Pardamean Negeri Asih, Simalungun Regency. The method used in data collection is a questionnaire method (questionnaire), documentation method, observation or observation. The questionnaire method is used to obtain information from respondents, the type of questionnaire is indirect and closed, namely the type of questionnaire that has provided answers. Data analysis technique using Chi Square. Based on the results of the study, it shows that the contingency coefficient value of 16.91 has been obtained after being compared with the product moment table, then it is greater than the "r" table at a significant level of 5% (9.488). So that the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected. This shows that there is a significant influence of learning discipline on social studies learning outcomes for fifth grade students at SD Negeri 091523 Pardamean Negeri Asih, Simalungun Regency, in the 2022/2023 academic year.